#
Proof: A(log B) = log (B^A), log A - log B = log (A/B)

Proofs of the logarithm properties: A(log B) = log (B^A) and log A - log B

If you're seeing this message, it means we're having trouble loading external resources on our website.

If you're behind a web filter, please make sure that the domains ***.kastatic.org** and ***.kasandbox.org** are unblocked.

Main content
#
Proof: A(log B) = log (B^A), log A - log B = log (A/B)

Proofs of the logarithm properties: A(log B) = log (B^A) and log A - log B